PERENCANAAN ULANG RODA GIGI PINION PADA GARDAN BELAKANG KENDARAAN JEEP BJ-212 - Wijanarko, Heri; Sugihandoko; Aryananta Lufti (JURNAL MEKANIKASISTA, 2025)
Gears function to transmit high power and precise rotation through interlocking teeth. Gears are superior to other transmission systems as they are more compact, capable of transmitting large power with high efficiency, and have a minimal risk of slipping. Additionally, gears can withstand higher loads and allow for speed variations as needed. One commonly used type is the bevel gear, where the pitch surface forms a cone with its apex at the intersection of the shaft axes. Straight bevel gears are the easiest to manufacture and frequently used, although they produce significant noise due to their low contact ratio. Other types of bevel gears include spiral bevel gears, helical bevel gears, and hypoid gears, each with unique characteristics and advantages in transmission systems.